Optimalisasi Manajemen Risiko Dalam Pinjaman Peer-To-Peer Yang Sesuai Syariah: Analisis Komprehensif Lanskap Fintech Syariah - Nur Hadhi Abbas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to evaluate risk management in financing through the Sharia Fintech Peer To Peer Lending (P2P) platform. P2P lending is an innovation in the financial sector that allows borrowers and fund providers to interact directly via digital platforms. In the context of sharia finance, the risk management aspect is crucial to ensure compliance with sharia principles. This research uses qualitative and quantitative analysis methods to identify and evaluate various aspects of risk management related to financing through sharia P2P lending. Risk factors such as credit risk, liquidity risk, operational risk and sharia risk will be evaluated to provide a thorough understanding of the effectiveness of risk management in this context.